Dietary ε-Polylysine Affects on Gut Microbiota and Plasma Metabolites Profiling in Mice - Zhang, Xuelei; Xu, Baoyang; Hou, Zhenping; Xie, Chunlin; Niu, Yaorong; Dai, Qiuzhong; Yan, Xianghua; Wu, Duanqin (Frontiers in Nutrition, 2022)
Given the antibacterial effects of ε-polylysine acting on cell membranes, and that glycerol phospholipids are important components of the cell membrane, we hypothesized that ε-polylysine may regulate glycerophospholipid metabolism by modifying the gut microbiota. To test this hypothesis, we treated post-weaning C57 mice with different levels of ε-polylysine (0, 300, 600, and 1200 ppm) in their basic diet. The growth performance and morphology of intestine were then determined. Modification of the gut microbiota and their function were analyzed using 16S rDNA sequencing. Metabolite identification was performed using the LC-MS method. The results showed that body weight decreased with an increasing supplemental level of ε-polylysine from 5 w to 7 w (P < 0.05), but no significant difference was observed after 8 w (P > 0.05). Supplementation with 1200 ppm ε-polylysine changed the morphology of the jejunum and ileum, increased the villus length, decreased the crypt depth of the jejunum, and decreased the villus length and crypt depth of the ileum (P < 0.05). ε-Polylysine shifted the intestine microbiota by changing alpha diversity (Chao 1, observed species, Shannon, and Simpson indices) and varied at different times. ε-polylysine decreased Firmicutes and increased Bacteroidetes at 4 w, but increased Firmicutes and decreased Bacteroidetes at 10 w. ε-Polylysine regulated genera associated with lipid metabolism such as Parabacteroides, Odoribacter, Akkermansia, Alistipes, Lachnospiraceae UCG-001, Collinsella, Ruminococcaceae, and Intestinimonas. During the adult period, the genera Alistipes, Lachnospiraceae UCG-001, and Streptomyces were positively associated with PC, PE, LysoPC, LysoPE, 1-Arachidonoylglycerophosphoinositol and OHOHA-PS (R > 0.6, P < 0.001), but changes in Blautia, Christensenellaceae R-7 group, Odoribacter, Allobaculum, Ruminococcaceae UCG-004, Ruminococcaceae UCG-005, and Lachnospiraceae UCG-010 were negatively correlated with glycerophospholipid metabolites (R < -0.6, P < 0.001). The abundance of glycerophospholipid metabolites, including PC, PE, lysoPC, and lysoPE, was decreased by ε-polylysine. Furthermore, ε-polylysine reduced the incidence of the genera including Ruminococcus, Prevotella, Prevotellaceae, Butyricimonas, and Escherichia-Shigella and reduced the abundance of Faecalibaculum, Christensenellaceae R-7 group, Coriobacteriaceae UCG-002. In conclusion, ε-polylysine modified gut microbiota composition and function while also restraining pathogenic bacteria. The glycerophospholipid metabolism pathway and associated metabolites may be regulated by intestinal bacteria.